Free Radical Scavenging Activity of Chlorochalcones: An Integrated Computational and Experimental Study - Puspitasari, Anita Dwi; Ulfah, Maria; Hartati, Indah; Vifta, Rissa Laila; Hermawan, Faris; Ekasari, Munifilia; Marlina, Lala Adetia (Universitas Gadjah Mada, 2025)
Chlorochalcone derivatives (chalcones 1–3) were synthesized using ultrasound-assisted Claisen-Schmidt condensation, yielding > 80%. Antioxidant activity was evaluated through DPPH and ABTS assays, demonstrating strong activity with IC50 values ranging from 61.52 ± 0.97 to 98.27 ± 1.42 ppm. Chalcones 1 and 2 show SPF potential at 40 ppm and chalcone 3 at 20 ppm (SPF 19.47 ± 0.46). ADMET analysis using the pkCSM tool confirmed favorable pharmacokinetic profiles and low toxicity, supporting their safety for potential applications. Additionally, density functional theory calculations provided more profound insights into molecular stability and reactivity, including electronic properties such as HOMO-LUMO gaps, further corroborating their pharmacological efficacy. These results collectively indicate that chalcones 1–3 exhibit potent antioxidant activity, adequate UV protection, and promising pharmacokinetic properties. Integrating in vitro, in silico, and DFT analyses underscores their potential as multifunctional compounds for antioxidant and sunscreen applications.